224k views
1 vote
Can someone show me how to do this or like just do a single problem for me to show me how to do it I don’t understand how to do the work but I know the answer please I need help it’s due tommarow

Can someone show me how to do this or like just do a single problem for me to show-example-1
User Spannerj
by
6.2k points

1 Answer

4 votes

Explanation:

The coordinates of the midpoint are the average of the endpoints.

40. Endpoint (-8, 11), and midpoint (-6, 9).

-6 = (x + -8) / 2

-12 = x − 8

x = -4

9 = (y + 11) / 2

18 = y + 11

y = 7

The other endpoint is at (-4, 7).

User Tammen
by
5.3k points